Insect Management for Sweet Potatoes - Xavier Martini; S. E. Webb (EDIS)
Sweet potatoes, both orange- and white-fleshed varieties, are widely grown in Florida. Foliar pests, leafminers, whiteflies and armyworms, are generally not difficult to manage; in fact insecticides should be avoided to conserve their natural enemies. More serious are those pests whose immature stages feed on roots: sweetpotato weevil, wireworms, banded cucumber beetles, pale-striped and sweetpotato flea beetles, and in south Florida, Diaprepes weevils and white grubs.